Magnéli phase titanium suboxides by Flash Spark Plasma Sintering. (15th March 2018) - Yu, Min; Saunders, Theo; Grasso, Salvatore; Mahajan, Amit; Zhang, Hangfeng; Reece, Mike John
Abstract: A Flash Spark Plasma Sintering (FSPS) technique was used to fully densify Magnéli phase titanium suboxides (95%TD) in 9 s. A modified FSPS setup contributed to produce homogeneous and dense microstructures, thus avoiding undesired residual porosity at the contact surfaces between samples and electrodes. FSPSed samples retained the original phases (Ti4 O7, Ti5 O9 and Ti6 O11 ) of the starting powder, whereas Ti4 O7 disappeared in those samples densified using Conventional Spark Plasma Sintering (CSPS). Compared to CSPSed samples, FSPSed ones possessed higher room-temperature electrical conductivity (1558 S·cm − 1 ). FSPSed sample exhibited good thermoelectric properties with a figure of merit (ZT) of 0.085 at 1073 K. Graphical abstract: Image 1